EFEKTIVITAS PENGGUNAAN REBUSAN AIR SIRIH HIJAU TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI UPT PUSKESMAS KOTA GARO KABUPATEN KAMPAR - Ariani, Yeyen; Tanberika, Fajar Sari; Ruspita, Rika; Yanti, Rifa (Ensiklopedia of Journal, 2025)
Perineal wounds are a common condition experienced by postpartum mothers due to birth canal tears or episiotomy, which, if not properly managed, can lead to infection, prolonged pain, and impaired activity. One traditional treatment believed to be effective is the use of green betel leaf decoction, which contains natural antiseptic compounds. This study aims to determine the effectiveness of green betel leaf decoction in healing perineal wounds in postpartum mothers at UPT Puskesmas Kota Garo, Kampar Regency. This is a quantitative study using a quasi-experimental design with a one-group pretest-posttest approach. The research was conducted in May 2025 with a sample size of 21 participants. The research instrument was an observation sheet using the REEDA scale. Data analysis was performed using univariate and bivariate analysis with the Wilcoxon test. The results showed that before the intervention, 61.9% of mothers had poor wound healing. After the intervention, the condition significantly improved, with 71.4% showing good wound healing. Statistical analysis showed a p-value = 0.000 (p < 0.05), indicating a significant difference before and after the use of green betel leaf decoction. It can be concluded that green betel leaf decoction is effective in accelerating the healing of perineal wounds. It is recommended that UPT Puskesmas Kota Garo adopt this method as a safe and natural non-pharmacological alternative in postpartum care.Keyword : Green Betel Leaf Decoction, Perineal Wound, Postpartum Mothers